Blended learning and application of web tools for materials engineering: a case study / Dian Darina Indah Daruis and Norshima Zainal Shah - Daruis, Dian Darina Indah; Zainal Shah, Norshima (UiTM Press, 2016)
The present study aims to examine students' perception of online learning through the university's Learning Management System (LMS) as opposed to free online LMS and free web tool environment which allow blended learning. Subjects involved are the students of the Materials Engineering course in semester 1, 2014/2015 session. 28 students enrolled for the course but only 21 students responded to the survey. Apart from an online short survey, data were collected from the available learning tracks, where blended learning was carried out using both the university's and free online LMSs. It was found from the learning track evidence that the majority of the students used resources from Blendspace many times more (more than 80%) than the LMS, when the same resources were made available at both platforms. The result from the self-reported survey also supported this trend where the majority of respondents agreed that they preferred the free web tools compared to the university's LMS. On the other hand, the academic staff when asked about the issues of teaching and learning with technologies claimed that their preference for the free web tools is mainly because the platforms are more interactive and attractive compared to the university's LMS. The study shows that the efficacy of e-learning depends on the students' buy-in as the majority of them claimed that although they feel more engaged through e-learning, they still prefer face-to-face learning.